Pengaruh Motivasi dan Disiplin Kerja Terhadap Peningkatan Produktifitas Kerja Karyawan PT. Ritra Cargo Medan - Nurhayati Nurhayati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine whether there is an effect of motivation and work discipline on increasing work productivity of employees of PT. Ritra Cargo Medan with a population and sample of 30 people. Data collection techniques used in this study were observation, interviews and questionnaires. After the data is obtained, the data processing uses multiple linear regression SPSS 21 application program, the coefficient of motivation regression (b1) is 0.241, the regression coefficient of work discipline (b2) = 0.550 and the regression constant a = 5.224. Using the t-test of motivation (X1) by comparing tcount with ttable obtained tcount = 1,747 < ttable = 2,048. So it can be concluded that the motivation variable (X1) has no effect on work productivity (Y). And the t-test of work discipline (X2) by comparing tcount with ttable obtained tcount = 4,281 > ttable = 2,048. So it can be concluded that the work discipline variable (X2) has a significant and significant effect on work productivity (Y). The F test is carried out by comparing the results of Fcount with Ftable. The value of Fcount = 26,172, while for the Ftable with a significant level of = 0.05, the value of Ftable = 3.354 (table F Statistics) is obtained. It can be seen that Fcount = 26,172 > Ftable = 3,354. So it can be concluded that the motivation variable (X1) and work discipline (X2) have a positive and significant effect on work productivity (Y)